2016
DOI: 10.1002/mren.201600044
|View full text |Cite
|
Sign up to set email alerts
|

Ethylene Polymerization with a Hafnocene Dichloride Catalyst Using Trioctyl Aluminum and Borate: Polymerization Kinetics and Polymer Characterization

Abstract: The polymerization of ethylene is investigated in a semibatch solution reactor using bis(n‐propylcyclopentadienyl)hafnium dichloride catalyst and tetrakis(pentafluorophenyl) borate dimethylanilinium salt ([B(C6F5)4]−[Me2NHPh]+) as the catalytic system. Trioctylaluminum (TOA) is used as impurity scavenger and alkylating agent. Ethylene pressure, polymerization temperature, TOA, borate, and catalyst concentrations are changed to investigate ethylene polymerization kinetics with this catalyst system. A 23 central… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…In previous publications from our group, , the effects of activating rac- dimethylsilyl­bis­(indenyl)hafnium dimethyl with MAO or tetrakis­(penta­fluorophenyl) borate dimethyl­anilinium salt were compared using statistical techniques to estimate the main polymerization kinetic parameters for these systems. This line of research was extended in a subsequent publication to study the kinetics of ethylene polymerization using the bis­( n -propylcyclo­pentadienyl)­hafnium dichloride/borate/TOA system . The present investigation continues our efforts to elucidate these intriguing systems by by providing additional details on the copolymerization of ethylene and 1-hexene using bis­( n -propylcyclo­pentadienyl)­hafnium dichloride (HfCl 2 ) and bis­( n -propylcyclo­pentadienyl)­hafnium dimethyl (HfMe 2 ) activated with tetrakis­(pentafluoro­phenyl) borate dimethyl­anilinium salt (B), in the presence of trioctylaluminum (TOA).…”
Section: Introductionmentioning
confidence: 70%
See 3 more Smart Citations
“…In previous publications from our group, , the effects of activating rac- dimethylsilyl­bis­(indenyl)hafnium dimethyl with MAO or tetrakis­(penta­fluorophenyl) borate dimethyl­anilinium salt were compared using statistical techniques to estimate the main polymerization kinetic parameters for these systems. This line of research was extended in a subsequent publication to study the kinetics of ethylene polymerization using the bis­( n -propylcyclo­pentadienyl)­hafnium dichloride/borate/TOA system . The present investigation continues our efforts to elucidate these intriguing systems by by providing additional details on the copolymerization of ethylene and 1-hexene using bis­( n -propylcyclo­pentadienyl)­hafnium dichloride (HfCl 2 ) and bis­( n -propylcyclo­pentadienyl)­hafnium dimethyl (HfMe 2 ) activated with tetrakis­(pentafluoro­phenyl) borate dimethyl­anilinium salt (B), in the presence of trioctylaluminum (TOA).…”
Section: Introductionmentioning
confidence: 70%
“…When catalyst deactivation and ethylene propagation rates follow first-order kinetics and also assuming that the site activation is instantaneous, the following equation describes ethylene uptake curves , where F M,in , is the molar flow rate of ethylene to the reactor, [M] is ethylene concentration in the liquid phase, [C i ] 0 is the initial catalyst concentration, and V R is the volume of the reaction medium. Equation can be linearized through the simple transformation …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We recently showed that a typical ion pair active species [(Cp Pr ) 2 HfMe]­[B­(C 6 F 5 ) 4 ] ( 3 Pr , Cp Pr = n -propyl-cyclopentadienyl ligand) undergoes selective activation of a propyl chain of a substituted Cp ligand, affording the thermally stable cyclometalated species [Cp Pr Cp CH2CH2CH2 Hf]­[B­(C 6 F 5 ) 4 ] ( 4 Pr ). , This in situ modification was proposed to contribute to multisite behavior observed for this and related catalysts. Due to the structural similarities of 4 Pr with an active catalytic species bearing a nascent polymeryl chain in which the last inserted unit is an ethylene molecule (Scheme ), we further explored the reactivity of 4 Pr with several CTAs. We succeeded to structurally characterize, through NMR spectroscopy and DFT calculations, a series of Hf–Al and Hf–Zn heterobimetallic adducts featuring inequivalent bridging alkyls and showed that these species are stabilized by multiple α-agostic interactions .…”
Section: Introductionmentioning
confidence: 99%